Graphene/polyaniline composite sponge of three-dimensional porous network structure as supercapacitor electrode - 姜久兴 张旭志 王振华 许健君 (Chinese physics B, 2016)
As a supercapacitor electrode, the graphene/polyaniline （PANI） composite sponge with a three-dimensional （3D） porous network structure is synthesized by a simple three-step method. The three steps include an in situ polymerization, freeze-drying and reduction by hydrazine vapor. The prepared sponge has a large specific surface area and porous network structure, so it is in favor of spreading the electrolyte ion and increasing the charge transfer efficiency of the system. The process of preparation is simple, easy to operate and low cost. The composite sponge shows better electrochemical performance than the pure individual graphene sponge while PANI cannot keep the shape of a sponge. Such a composite sponge exhibits specific capacitances of 487 F.g-1 at 2 mV/s compared to pristine PANI of 397 F.g-1.